2016
DOI: 10.1073/pnas.1525356113
|View full text |Cite
|
Sign up to set email alerts
|

S1PR1-mediated IFNAR1 degradation modulates plasmacytoid dendritic cell interferon-α autoamplification

Abstract: Blunting immunopathology without abolishing host defense is the foundation for safe and effective modulation of infectious and autoimmune diseases. Sphingosine 1-phosphate receptor 1 (S1PR1) agonists are effective in treating infectious and multiple autoimmune pathologies; however, mechanisms underlying their clinical efficacy are yet to be fully elucidated. Here, we uncover an unexpected mechanism of convergence between S1PR1 and interferon alpha receptor 1 (IFNAR1) signaling pathways. Activation of S1PR1 sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 29 publications
4
48
0
Order By: Relevance
“…However, the sphingosine analogs or S1P 1 R agonist could regulate cytokine responses during influenza virus infection (5760). Also, it was recently reported that the agonist of S1P 1 R or exogenous S1P can directly induces degradation of type I IFN receptor (IFNAR) to inhibit IFN amplification on plasmacytoid dendritic cells (61). This could be an important mechanism for the regulation of inflammatory response, given that S1P has been shown to affect cytokine/chemokine responses in diverse conditions (6264).…”
Section: Discussionmentioning
confidence: 99%
“…However, the sphingosine analogs or S1P 1 R agonist could regulate cytokine responses during influenza virus infection (5760). Also, it was recently reported that the agonist of S1P 1 R or exogenous S1P can directly induces degradation of type I IFN receptor (IFNAR) to inhibit IFN amplification on plasmacytoid dendritic cells (61). This could be an important mechanism for the regulation of inflammatory response, given that S1P has been shown to affect cytokine/chemokine responses in diverse conditions (6264).…”
Section: Discussionmentioning
confidence: 99%
“…Auto-traced outlines of the cells were used as regions of interest from which the total signal above background was extracted for the IL-1β signal. The total cellular area and mean fluorescence intensity of IL-1β in each cell was scored and plotted as integrated density (ID) (average area × mean fluorescence intensity/100), which was estimated separately for approximately 800 neurons and 200 microglial cells per section The average ID/cell per section for 3–4 sections from each mouse, containing both the left and right hemisphere CeA, was used for statistical analysis and graphing 4750 .…”
Section: Methodsmentioning
confidence: 99%
“…4H). Thus, S1PR1 agonist prevented T1D by suppressing IFN-α signaling (20,24), restricting the migration of antiself T cells to geographic areas outside the islets and likely by contributing to T-cell exhaustion through up-regulation of negative immune regulators like PD-1 and LAG3.…”
Section: Comparable Gene Expression In the Pancreatic Islets Is Observedmentioning
confidence: 97%
“…Sphingosine-1-phosphate receptor 1 (S1PR1) agonists like CYM-5442 modulate lymphocyte trafficking and significantly alter IFN-α autoamplification acting primarily on pDCs to reduce IFN-α expression by promoting the turnover of IFNAR at the cell surface, resulting in reduced STAT1 phosphorylation and inhibition of type I IFN autoamplification (20). To determine whether modulation of the S1PR1 signaling would abort the development of T1D, Rip-LCMV tg mice infected with virus and receiving daily administration of CYM-5442 (10 mg/kg) showed normal blood glucose levels over a 21-d observation period compared with isotype control in which four out of five mice displayed diabetic levels (>250 mg/dL) by day 10 p.i.…”
Section: Ifn-α But Not Ifn-β Is a Required Signal For Autoreactive mentioning
confidence: 99%
See 1 more Smart Citation